Grit and student adjustment in Islamic boarding schools: Peer support as moderator - Muallifah, Muallifah; Qomi Akit Jauhari, Qomi Akit Jauhari; Serly Amria, Serly Amria; Ilhamuddin, Ilhamuddin; Ilhamuddin , Ilhamuddin (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2025)
Previous research has addressed the relationship between grit and student adjustment. However, the understanding of the influence of internal factors on adjustment capacity remains limited. Therefore, this study aimed to analyze whether peer support can moderate the relationship between grit and student adjustment. This study used a correlational quantitative approach. This study used multiple regression with Moderated Regression Analysis (MRA) using JASP 18.3.0. The research sample was 314 students at the Islamic boarding school in Malang, Indonesia. The study's results showed a significant influence of grit on school adjustment, with a p-value of 0.001. Meanwhile, the results of the moderation analysis showed that the peer support significantly moderated the relationship between grit and student adjustment. The value of the negative interaction coefficient indicated that as peer support increases, the relationship between grit and student adjustment actually decreased. The implications of this study suggested that grit plays a significant role in student adjustment in Islamic boarding schools, but this effect weakens as peer support increases, acting as a negative moderator. This research emphasizes the need for a balanced coaching strategy that focuses on strengthening grit and managing peer support to help students adjust optimally.